Fun with Clothes Project Book: 4HCCM10/4H115, 6/2002 - Armstrong, Shona; Pourciau, Johannah; Jordan, Joy Cantrell; Hackler, R. Nadine (EDIS, 2002)
This document is 4HCCM10 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published in 1994; Reviewed June 2002. https://edis.ifas.ufl.edu/4h115